Mixed Lung Cancer in 46 Years Old, Male Smoker, Untreated Patient - Susilorini, Susilorini; Puspasari, Dik; Amarwati, Siti; Endro, Bambang (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2016)
Lung cancer is a large heterogeneous family of malignancies, with tumors containing more than one subtype are very common. Over 50 different histological variants are recognized within the WHO typing system. Small Cell Lung Cancer comprises approximately 20% of all lung cancers and exhibits a neuroendocrine phenotype while Non Small Cell Lung Carsinoma (NSCLC) lacks these features and makes up the remaining 80% of cases. This case was reported in view of the rarity of this combination of morphologic patterns. The incidence of c- SCLC (Combined- Small Cell Lung Carsinoma) has been reported ranging from less than 1% to 14.6% of all SCLC. Mixed lung cancer in untreated patients suggests a common endodermal origin for c-SCLC which contains small-cell and non-small-cell pulmonary tumors. Quoix et al found that presentation as a solitary pulmonary nodule (SPN) is particularly indicative of a c-SCLC. Combined- Small Cell Lung Carsinoma contains a squamous cell and/or adenocarcinoma component. It’s becoming more important for pathologists to correctly subclassify NSCLC’s as distinct tumor entities, or as components of c-SCLC cause it’s more agrresive. A 46-year-old smoker man was referred because of rapid growth of a solitary nodule mass revealed by chest radiography with brain and limfonodes metastases. There was mixed histological feature including adenocarsinoma, squamous cell carsinoma and large cell carsinoma. The patient is dead after a few weeks later. It was revealed a panel immunohistochemistry stain (CK-7, CK-20, TTF-1, P63 and Chromoganin). It was concluded as c- SCLC.